Women's Rights in the Saudi Labor Law - Ahlam Saad Abdullah Al-Zahrani,; Amal Mohammed Shalabi Khadji, (International Journal of Law Research and Studies, 2025)
This study examines the rights of working women in the Saudi system and analyzes the extent to which relevant authorities are committed to implementing them, with a focus on legislative developments related to the Kingdom's Vision 2030. The study adopted an analytical approach to the Saudi labor system and reached several conclusions, most notably: the system guarantees women various rights, including equal pay, prohibiting discrimination, maternity leave, protection from dismissal during pregnancy, and the provision of a safe work environment. Despite these guarantees, the study revealed disparities in actual implementation, especially in small and medium-sized enterprises (SMEs), and limited women's awareness of their rights. The study recommended strengthening government oversight, improving legal awareness programs, simplifying complaints procedures, imposing stricter penalties on violators, developing an electronic system for reporting violations, and providing accessible legal advice to working women. It also focused on empowering women in leadership positions to overcome the cultural challenges they face in the labor market.
Keywords: Women's Rights; Working Women; Saudi Labor System